‘Isolation(s)’, ‘Unevent’, and ‘Prosthetic Memory’: A study on Digital Archives in Post-Pandemic India - C P, Greeshma (Literary Studies, 2023)
With the onset of covid-19 in India, the digital and the memory associated with the digital-visual reached yet another perplexing phase. Visual complexity (Jay 95) and ‘tacit knowing’ (Polanyi 34) that we seem to have transcended-crystallised into digital chaos, reinforcing and restructuring ‘the macula’ especially with the onset of Covid 19 in India. The "bio-bubble" fundamentally warped and validated our perception of reality in relation to digital screen time- shifting ‘meaning- making’ immediately online. The pandemic further condensed what Shoshana Zuboff calls the ‘behavioural surplus’, where our already broadcasted privacy into the global data ecosystem determining our ‘everyday’ transformed into inevitable structures of security and sustenance. This ‘architecture of oppression’ nullifies the chaos and deconstructs ‘event-oriented sense of time’, essentially locating us in a historical ‘moment of danger’ where we are trapped in a targeted, polarized, manipulated, pandemic-reconfigured urban digital space. This sudden and induced economies of isolation(s) further question the boundaries and reception of individual digital space in the global village. The "eventful" that happened outside of the digital world swiftly dissolved into a series of "unprecedented happenings" that we had to access online, gradually liquefying into numerous far-off "unevents." The paper therefore intends a textual study of these isolation(s) through a few journalistic photographs and digital archives of the pandemic in India and enquire into the possibilities of utilizing them as tools of ‘microhistory’ in ‘the uneventful’ digital milieu. An attempt to examine the mediation between individual digital mobility, digital archives, and collective prosthetic memory in reclaiming ‘the oppressed past’ from ‘homogenous empty time’ is also being made.